Physical and Mechanical Properties of Fly Ash-Bottom Ash Geopolymer Mixtures on Expansive Clay Soil Stabilization as a Subgrade Material - Wijaya Miguel Felix; Ismanti Sito; Satyarno Iman (Civil and Environmental Engineering)
The presence of expansive clay causes roads to undergo damage such as wavy, cracked, and even potholes. This type of soil shows that the soil is prone to swelling and shrinking. A base soil handling method against the effects of swelling and shrinking is chemical soil stabilization such as mixing the soil with lime, cement or additional materials. In this study, the stabilization method used was the fly ash and bottom ash geopolymerization reaction. Fly ash and bottom ash is an effective alternative to replace cement. Fly ash and bottom ash with addition of alkali activators of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) can serve as a binder similar to cement. This study aimed to improve the physical property and mechanical property tests of the soil such as bearing capacity and swelling potential as a requirement for subgrade. All physical property test results revealed that using fly ash-bottom ash geopolymer paste can improve qualities such as specific gravity, Atterberg limit, and grain size to improve expansive clay soil. Likewise, the mechanical property test results showed that the subgrade stabilized with fly ash-bottom ash geopolymer can increase its strength to surpass the requirements for road subgrades.